Profile Comparison of Patient with Staphylococcus epidermidis and Staphylococcus aureus on Blood Specimen at Dr. Moewardi Hospital - Gani Dwi Cahya; Marwoto .; Dhani Redhono Harioputro (Nexus Biomedika, 2016)
Introduction: Staphylococcus epidermidis and Staphylococcus aureus are some of bacteria that are often found in blood specimen. Unlike Staphylococcus aureus, which is true pathogen, Staphylococcus epidermidis is known as opportunistic bacteria which actually are normal flora of human skin. Therefore, it is necessary to have comparative data that can determine whether Staphylococcus epidermidis are cause of infection or just colonization. The purpose of this research was to compare clinical profile of patients with Staphylococcus aureus and Staphylococcus epidermidis found in blood specimen. Methods: This study was a descriptive research using clinical epidemiology approach. The objects of the research were patients medical records which had been identified by blood culture with positive result of Staphylococcus epidermidis and Staphylococcus aureus on 2014-July 2015. Sampling was held during November and December 2015 at Dr. Moewardi Hospital, Surakarta. Sampling was done and 65 people taken from the population. The data were analyzed with frequency odds ratio. Results: During January 2014 - July 2015, it was found that 36 subjects of patients with positive Staphylococcus epidermidis (21 men, 15 women) and 29 subjects of patients with positive Staphylococcus aureus (11 men, 18 women). Staphylococcus epidermidis was mostly found in newborns dan infants, while Staphylococcus aureus was mostly found in adults and elders. The result of white blood count and neutrophil percentage showed that patients with positive Staphylococcus aureus on their blood specimen have higher value than Staphylococcus epidermidis. Vital sign showed higher mean value of body temperature on patients with positive Staphylococcus aureus on their blood specimen than Staphylococcus epidermidis. Conclusion: There were differences in the increase of body temperature, number of leukocytes, and percentage of neutrophils in patients profile who were exposed to Staphylococcus aureus and Staphylococcus epidermidis on blood specimens at Dr. Moewardi Hospital. Keywords: Blood Specimen, Blood Culture, Staphylococcus aureus, Staphylococcus epidermidis